All Questions Topic List
Limits Questions
Previous in All Question Next in All Question
Previous in Limits Next in Limits
Question Number 121302 by liberty last updated on 06/Nov/20
(1)limx→0(1−e2x)sin(3x)∣4x∣?(2)limx→0⌊(1−e2x)sin3x∣4x∣⌋?
Answered by bemath last updated on 06/Nov/20
(1)limx→0(1−e2x)sin3x∣4x∣limx→0−(1−e2x)sin3x−4x=limx→0−3cos3x(1−e2x)−2e2xsin3x−4=0limx→0+(1−e2x)sin3x4x=limx→0+3cos3x(1−e2x)−2e2xsin3x4=0
Answered by Bird last updated on 06/Nov/20
letf(x)=(1−e2x)sin(3x)4∣x∣wehavee2x∼1+2xandsin(3x)∼3x⇒f(x)∼−2x(3x)4∣x∣=−6x24∣x∣=−32∣x∣⇒limx→0f(x)=0
Terms of Service
Privacy Policy
Contact: info@tinkutara.com